Načrtovanje projektov digitalizacije v Mariborski knjižnici kot oblika medinstitucionalnega sodelovanja na območju - Hriberšek Vuk, Nina (Knjižnica, 2012)
More and more Slovenian public libraries have been facing the question of selection criteria for digitisation of library materials as well as the issue of financial resources, copyright permission and the promotion of digitised materials. Libraries having long tradition of collecting valuable local history resources are more convinced about the selection criteria. Digitisation is, in spite of being expensive, time consuming and labour intensive, an easy method to enable quick access to library materials, to promote and preserve library collections. The mission of the central regional public library (co)financed by the Ministry of Culture is not only to coordinate the collection, cataloguing and storage of local history resources but also to coordinate local history digital projects. Due to historical circumstances, the local history resources were first collected by the Maribor University Library. It is only in the recent past that the Maribor City Library has started to systematically collect these materials. Due to this fact, the Maribor City Library does not hold an extensive collection of rare and valuable local history items. It was initially faced with the problem of selection criteria for digitisation. However, it soon succeeded to establish the strategy to promote the local history collections in the region, regardless of their location. Thus the library started to cooperate with different regional institutions and the first partner projects were designed. In the year 2007 the library collaboratedwith the elementary school at Lovrenc na Pohorju and decided to digitise research papers of ex-pupils of the school. The first part of the project was accomplished in 2007 when 72 research papers were digitised, in the next two years their number was increased as the second part of the project was concluded. The papers were published on the KAMRA portal and the project was promoted at the summer annual meeting at Lovrenc na Pohorju. The next project was initiated in coopeartion with the Vurberk Tourist Association who contributed the photos for the exhibition about the Vurberk castle held at one of the branch libraries at Duplek. The Tourist Association was interested in the digitisation of their collection. Our partnership was extended to the Ivan Potrč Library of Ptuj and the Maribor University Library. In 2010 46 photos of the castle and the sanatorium of pulmonary disease, which was located in the castle during the second war, were digitised together with 12 postcards dating at the end of 19th and the beginning of the 20th century, and five older books about Vurberk. At first these items were accessible via dLib.si portal and later via the KAMRA portal, too. Although the Maribor City Library does not digitise such a large portion of library collection as other public libraries, it tries to cooperate in project and ensure access to local history collections held by regional institutions. The partnership with the Maribor Regional Archive was to be established in 2012. A selection of materials of the former Tovarna avtomobilov Maribor (TAM) was planned to be digitised. The factory was the leading national truck manufacturer in the post war period. However, it was ruined at the end of the 20th century. A lot of local families were related to the factory. Because of the actuality of the theme, it is hoped that the project will reach its primary goal to attract a wide range of people.
Keywords: splošne knjižnice; Mariborska knjižnica; digitalizacija; digitization; spletni portali; projekti; sodelovanje